Efectos de la radiación no ionizante emitida por dispositivos inalámbricos - Esquivel Rodríguez, L. J.; Alvarado C., Rafael; Mota Hernández, Cinthya; Santos R., Jaime R. (Visión electrónica, 2013)
The use of portable electronic equipment that emits non-ionizing radiation in the electromagnetic spectrum increases steadily and marks a trend likely to integrate functionality and miniaturization. Particularly, cellular telephony is widely used all around the world by a large number of users, despite little is known about the effects they may have on human health or that provides certainty about the results obtained. Many studies and projects to investigate those have been carried out, some have reached alarming results DNA breaks, genotoxicity, while others found no potential or significant threats and namely the results are not conclusive. The investigation document presents an analysis of previous specialized documentation, developed by recognized organizations in order to promote and enhance the discussion of the topic, considered polemical.